Electrode Kinetics and Thermodynamics Study of 2,3-Dihydroxy Pyridine Complexes of Pd(II) at DME in Vicinity of Khetri Copper Mines in Rajasthan - Sharma, Jaswant; Mukherjee, S.K. (Asian Journal of Chemistry, 2010)
The kinetic parameters and formation constant of palladium- pyridine complexes were determined polarographically by De Ford/Hume graphical extrapolation method and method Mihailov's mathematical method respectively. The thermodynamic parameters ( ΔFo, ΔHo and ΔSo) were also determined.